Microwave propagation in dust storms: a review - Bashir, Saad Osman; McEwan, N.J (IEE, 1986)
A review is given of the literature covering the effects of dust storms on microwave links. Most authors have calculated the effects of absorption of energy, revealing that it is not very significant unless very high suspended dust densities are assumed. A few papers indicate the possibility of more significant cross polarisation. Air refractive effects associated with dust storms have been relatively neglected but are strongly indicated by observations. Note: CITED BY 34